1988
DOI: 10.1111/j.1399-3054.1988.tb09182.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic oxygen species and protective systems of the chloroplast

Abstract: Salin, M. L. 1988. Toxic oxygen species and protective systems of the chloroplast. -Physiol. Plant. 72: 681-689.As a consequence of living in an environment enriched in oxygen, which they themselves at least partially generate, photosynthetic organisms are exposed to large fluxes of oxyradicals and reactive oxygen species. Among these are superoxide, hydrogen peroxide, hydroxyl radical and singlet oxygen. These highly reactive intermediates pose the threat of toxicity unless neutralized by scavenger substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
217
0
8

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(228 citation statements)
references
References 66 publications
3
217
0
8
Order By: Relevance
“…The antioxidant activity of ascorbate is dependent upon its regeneration ability and DHAR catalyzes the re-reduction of dehydroascorbate to ascorbate by glutathione [51]. Enhanced DHAR activity, against oxidative stress, has also been reported [52,53]. In addition, Urano et al [51] observed that DHAR activity rapidly increased in rice during heat stress and suggested that DHAR was involved in protection against high temperature.…”
Section: Redox Homeostasismentioning
confidence: 99%
“…The antioxidant activity of ascorbate is dependent upon its regeneration ability and DHAR catalyzes the re-reduction of dehydroascorbate to ascorbate by glutathione [51]. Enhanced DHAR activity, against oxidative stress, has also been reported [52,53]. In addition, Urano et al [51] observed that DHAR activity rapidly increased in rice during heat stress and suggested that DHAR was involved in protection against high temperature.…”
Section: Redox Homeostasismentioning
confidence: 99%
“…H202 is the most stable of the ROls and can behave as both an oxidant and a reductant, although it has a low ability to react with most organic molecules if no metal catalysts are present (Salin, 1987). l h e electron transfer chain of the chloroplasts is the best-documented source of H, O, (Mehler, 1951 ;Asada, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…13 Plants have evolved a variety of mechanisms to deal with the damaging effects of ROS in cellular compartments, which are generally handled through the production of various antioxidative enzymes, such as superoxide dismutase (SOD) and peroxidase (POD). SOD can catalyze superoxide radicals (O 2…”
Section: ' Introductionmentioning
confidence: 99%